Mixed Reality in Therapeutic Education for Diabetes: Grayscale and Color Passthrough Compared with Augmented Reality and Traditional Methods - Marcelo Calle; Francisco Abad; M.-Carmen Juan (Applied Sciences)
This publication presents the development of a new mixed reality (MR) application for headsets, using grayscale and color passthrough to support therapeutic education in diabetes. Passthrough technology allows users to see their real-world environment through cameras on the headset. A comparative study was conducted to assess the effectiveness of our application in its two visualization modes against traditional learning and an augmented reality (AR) application. The study assessed the increase in patients’ knowledge of the carbohydrate content of different foods, as well as the usability of and satisfaction with each application, with 92 Ecuadorian patients with Type 1 diabetes participating. The results indicate that all four learning methods positively influenced patient increase in knowledge (post–pre). However, pairwise comparisons of post-knowledge scores showed that the MR color passthrough and AR applications significantly outperformed the traditional method, with patients using color passthrough achieving greater post-learning outcomes than those using grayscale or AR. Positive post-knowledge outcomes were observed across all age and gender groups. The patient feedback on their experience with the MR application using color passthrough was significantly higher than with the grayscale version. Therefore, while all methods demonstrated positive effects on knowledge gain, the findings presented in this publication suggest that color passthrough offers great potential for creating engaging, context-rich, and interactive learning environments that have a positive effect on both learning and user experience.